The translingual practices in the Indonesian-Spanish family’s communication showcased at a digital platform TikTok - Rachmi Rachmi; Maya Rohimah Atmawinata; Arjulayana Arjulayana (Universitas Muhammadiyah Malang, 2025)
This research studies the translingual practices enacted by an Indonesian-Spanish family within their daily communication, as demonstrated on the digital platform TikTok. Anchored in sociolinguistic theories of translanguaging, it explores the ways in which family members adeptly navigate and negotiate meaning across different languages, drawing upon their comprehensive linguistic and semiotic repertoires. Employing a qualitative methodological framework, the study scrutinizes conversational excerpts to elucidate how translingual practices such as envoicing, recontextualization, interactional negotiation, and entextualization operate as dynamic resources for the construction of identity, cultural expression, and the creation of relational meaning. The findings illuminate the family’s innovative and context-sensitive application of language, which surpasses conventional linguistic boundaries and contests monolingual frameworks. This research significantly enriches the understanding of bilingual speech production within intimate familial environments and underscores the importance of digital platforms as arenas where translingual communication is both enacted and disseminated. Furthermore, the study provides theoretical contributions by integrating the concepts of translanguaging space and spatial repertoires, thereby accentuating the ecological and mediated characteristics of language practices in contemporary multilingual contexts.